Surgical management of uterine niche in a patient with secondary infertility and successful pregnancy outcome - Devi, T. Ramani; Devi, C. Archana; Nethaji, Swati; Kaviya, E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine niche or caesarean scar defect is a known cause of secondary infertility and implantation failure. Surgical repair can restore uterine anatomy and improve fertility outcomes in selected patients. This case report presents a 38-year-old woman with a history of one lower segment caesarean section and two failed in vitro fertilization (IVF) cycles presented with secondary infertility. Ultrasound showed a prominent uterine niche. She underwent DHL with niche repair followed by controlled ovarian stimulation and intracytoplasmic sperm injection (ICSI). Frozen embryo transfer of two day 3 embryos resulted in a viable pregnancy. An elective repeat caesarean section was performed at 36 weeks + 4 days, resulting in the birth of a healthy infant. Laparoscopic niche correction may improve fertility outcomes in patients with uterine scar defects contributing to infertility, particularly those with prior IVF failures.